Humán tőke és nemzetközi karrierek - Gyökér, Irén; Finna, Henrietta (Közép-Európai Közlemények, 2013)
Economic and social developments in the last decades lead to value appreciation of human resources in counties’ competitiveness. In this paper we provide insight to a research which is focused on the global careers of qualified young Hungarians. The global careers, while strongly influenced by economic and historical developments, are also affected by the characteristics of the people and the domestic labor market, and by emigration and immigration issues. Upon closer look we find that the global careers of Hungarians take two major and distinctively different forms: self0initiated expatriation and the global careers initiated by major multinational players that support Hungarian employees to develop their knowledge and skills in another business unit in a different country within the same organization. Hungary’s primary interest would be to provide opportunities for spending time abroad for a wide range of the population, in order to obtain international exposure, experience and best practices, which in return could contribute to the national economic growth and a more competitive presence of Hungarians on the international market. For individuals having a global career is a great challenge, but at the same time it provides enduring benefits for their future career. Highly qualified young people who have gained experience and new competencies abroad have incentives to stay longer in their host country or not even return to the home country, which, from a human capital perspective, may negatively affect Hungary in the long run. Therefore we pay special attention to this group that is considered to be a strategic asset for the country.